Interaction of SF-1 and Nur77 proteins from a gonadotrope cell line with the promoter of the GnRH receptor gene : implications for gene regulation - Sadie, Hanel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.